Positron annihilation in boron nitride - Amrane, N. (Condensed Matter Physics, 2006)
Electron and positron charge densities are calculated as a function of position in the unit cell for boron nitride.
Wave functions are derived from pseudopotential band structure calculations and the independent particle
approximation (IPM), respectively, for electrons and positrons. It is observed that the positron density is maximum
in the open interstices and is excluded not only from ion cores but also to a considerable degree from
valence bonds. Electron-positron momentum densities are calculated for (001,110) planes. The results are
used in order to analyse the positron effects in BN. Електроннi i позитроннi зарядовi густини є обчисленi як функцiї положення одиничної комiрки для
нiтриду бору. Хвильовi функцiї отриманi, вiдповiдно, з обчислень псевдопотенцiальної зонної структури i наближених незалежних частинок (IPM) для електронiв i позитронiв. Спостережено, що позитронна густина є максимальною у вiдкритих щiлинах, i є обмеженою не тiльки iонним кором, але
також, значною мiрою, валентними зонами. Густини електрон-позитронного моменту обчисленi для
площин (001,110). Результати використанi для аналiзу позитронних ефектiв у BN.